Children with congenital limb deficiency in Norway: issues related to school life and health-related quality of life. A cross-sectional study. Issue 18 (27th August 2016) - Johansen, Heidi; Dammann, Brede; Øinæs Andersen, Liv; Andresen, Inger-Lise
Abstract: Purpose: To describe clinical features, issues related to school life and health-related quality of life (HRQOL) for children with congenital limb deficiency (CLD) and compare these children to Norwegian school children on HRQOL. Method: Cross-sectional study. In 2010, a postal questionnaire, designed for this study and the Paediatric Quality of Life Inventory (PedsQL), was sent to 154 eligible parents of children with CLD, aged 6–18 years and registered at TRS National Resource Centre for Rare Disorders in Norway. Results: Response rate 44% ( n  = 67), median age 11 years, 42% were girls. Of the total group, 46 had unilateral upper limb deficiency (UULD) and 21 had multiple/lower limb deficiency (MLD/LLD). The most common UULD was below-elbow deficiency, of these, 65% used grip-improving devices, and 35% used prostheses. Children with UULD-reported PedsQL score similar to Norwegian schoolchildren (NSC). The MLD/LLD group was heterogeneous; most had below-elbow/knee deficiency. In this group, PedsQL scores were reduced for physical and social functioning compared with NSC. Compared with children with UULD, more children with MLD/LLD were restricted in participation because of pain and fewer participated in physical education with peers. Conclusions: Most children with CLD participated with their peers and managed well in everyday life. Children with MLD/LLD seemed to have more challenges than children with UULD. Approximately one-third of all the children had assistive devices and/or practical assistance in school. Implications for Rehabilitation: Most children with upper-limb deficiency (UULD) in Norway manage well in everyday life and have HRQOL equal to other Norwegian children. Many choose grip-improving devices instead of prostheses. Their preferences should be respected and taken into account as the need for new assistive devices arise. For children with pronounced disabilities, access to, and use of, assistive devices, adaptions and practical assistance may be important for participation. Cooperation with the child and the parents is necessary to find useful measures. Physical education and practical subjects may provide special challenges, both for children and their teachers. Children themselves often find good solutions and the tasks should be planned ahead in cooperation with them.